Addressing stunting in Karangwangi: Optimal strategies for toddlers, adolescents, and pregnant women - Tamia, Ihsani; Fauzan, Raden Ardra Catur (Universitas Pendidikan Indonesia, 2024)
Stunting is a problem that requires more attention because it can have an impact on children's lives into adulthood, especially the risk of physical and cognitive developmental disorders if not appropriately handled. The service aims to educate the local community through collaboration between the Karangwangi Village PKK Movement Team, BKKBN, Karangwangi Village Health Center, and the Thematic KKN Team of Universitas Pendidikan Indonesia about the dangers of stunting and the importance of a clean and healthy lifestyle (PHBS). The community services were conducted based on the program that had been implemented on July 26-August 26, 2023 in Karangwangi Village through the methods of (a) direct discussion between students and TP-PKK for posyandu activities; (b) community education about stunting in the form of counseling, distributing printed media in the form of posters and brochures directly to counseling participants; (c) socialization to Karangsari Elementary School students regarding clean and healthy living behavior (PHBS); and (d) health checks in CEKAS activities, and POSBINDU-PTM. The results showed that Karangwangi Village is in a zero stunting condition; government programs and innovative activities support this, so it is expected to prevent and increase public understanding of the dangers of stunting in the Karangwangi Village community.